Scientific and practical justification of alternative methods for using the phytopreparations Hemostat and Clove Essential Oil in the treatment of severe chronic generalized periodontitis - Axmadovich, Sobirov Alijon; Amrulloyevich, Gafforov Sunatullo; o`g`li, Abdukholiqov Sirojiddin Fakhriddin; o`g`li, Xamrayev Mirali Sherali; Sotvoldiyevich, Djambilov Ravshanbek; Tuhtakhodjaevna, Nurmatova Nodira; o`g`li, Odiljonov Javokhir Dilmurodjon (Edelweiss Applied Science and Technology, 2025)
The widespread prevalence of periodontal tissue diseases, including severe chronic generalized periodontitis, has increased interest in the use of plant-based herbal remedies for treatment due to their safety and positive outcomes. The aim of this study was to treat severe chronic generalized periodontitis using the liquid extract of the herbal remedy "Hemostat" as an alternative. A total of 326 patients aged 41-60 years with a diagnosis of chronic generalized periodontitis (K05.5) were evaluated for periodontal tissue condition using a special chronological chart. Measurements were taken before treatment, as well as 10 and 20 days after treatment, based on eight clinical indicators: oral hygiene, quantitative and qualitative characteristics of the microflora of periodontal pockets, neutrophil infiltration, local allergic reactions, bleeding of periodontal pockets and gingival sulci, tissue repair, and atrophy of interproximal alveolar bone ridges. Observations based on these eight indicators during the treatment of severe chronic generalized periodontitis led to the conclusion that, for eliminating pathology, the clinical effectiveness of the integral indicators demonstrates the possibility of using alternative methods when selecting oral antiseptics: liquid extract of the herbal remedy "Hemostat" followed by "Clove Essential Oil" and, with satisfactory results, the synthetic drug "Chlorhexidine Bigluconate."